Potensi Teknik Pembelajaran Kooperatif Berbantu Whatsapp untuk Mengurangi Kecemasan Siswa dalam Berbicara Bahasa Inggris - Alberth Alberth (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Anxiety is one of the main inhibiting factors in using a foreign language, especially English. However, there is a relatively minimal amount of literature discussing the sources of this anxiety and techniques to reduce it. Although several previous studies have attempted to offer various solutions to overcome language anxiety issues in English, those solutions have proven to be less effective and unnatural. Therefore, more effective and natural solutions are needed to address this anxiety problem. This article aims to offer a solution to this problem through the utilization of cooperative learning techniques aided by WhatsApp. Examples of using cooperative learning techniques aided by WhatsApp will be discussed in this paper.